English Vlog Project: Students’ Perceptions and Their Problems - Fitria, Tira Nur (LPPM Universitas Advent Indonesia, 2022)
Vlogging can help language learners to practice even improve their speaking skills. This research is to know the non-English students’ perception and their problems of making an “English Vlog” project at ITB AAS Indonesia in 2020/2021. This research applies descriptive qualitative. The analysis shows that most students strongly agree that speaking is the most challenging skill. But, they agree that the English vlog is an interesting and fun task in English class in making them dare to speak in English. The topic/theme about